2011
DOI: 10.1212/wnl.0b013e318210435e
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke depression and treatment effects on functional outcomes

Abstract: Background: Poststroke depression (PSD) is common after stroke; however, the relationship to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 27 publications
3
51
0
Order By: Relevance
“…Anxiety and depression are common in people with stroke (Fure et al, 2006;Hackett et al, 2005;Pohjasvaara et al, 2001;Schmid, Kroenke, et al, 2011). In our study, we found a significant difference in anxiety scores between participants.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Anxiety and depression are common in people with stroke (Fure et al, 2006;Hackett et al, 2005;Pohjasvaara et al, 2001;Schmid, Kroenke, et al, 2011). In our study, we found a significant difference in anxiety scores between participants.…”
Section: Discussionsupporting
confidence: 41%
“…For example, balance impairment has been found to affect 83% of people with acute stroke (Tyson, Hanley, Chillala, Selley, & Tallis, 2006). Anxiety and depression are frequently observed in people with stroke (McGinnes, 2009), and depression has been found to be strongly associated with poor functional outcomes (Fure, Wyller, Engedal, & Thommessen, 2006;Hackett, Yapa, Parag, & Anderson, 2005;Pohjasvaara, Vataja, Leppävuori, Kaste, & Erkinjuntti, 2001;Schmid, Kroenke, et al, 2011). Activity and participation levels have also been found to be decreased after stroke (Hartman-Maeir, Soroker, Ring, Avni, & Katz, 2007;Mayo, Wood-Dauphinee, Côté, Durcan, & Carlton, 2002).…”
mentioning
confidence: 99%
“…Although data are inconclusive as to whether improvement of poststroke depression is independently associated with functional improvement, 222 depression can negatively affect a patient's ability to actively participate in rehabilitation therapies. 223 It is important to address symptoms early in the rehabilitation process, especially given the recent trend for less time in rehabilitation.…”
Section: Poststroke Depression Including Emotional and Behavioral Statementioning
confidence: 99%
“…As in previous studies, functional independence was defined as 0 to 2 (slight to no disability) and dependence was defined as 3 to 5 (moderate to severe disability). 26,27 Balance was assessed with the Berg Balance Scale (BBS), a 14-item physical performance measure of static and dynamic balance found to be reliable and valid after stroke. 28 Scoring ranges from 0 to 56, with higher scores indicating better balance.…”
Section: Outcome Assessmentsmentioning
confidence: 99%